The Impact of Quality and the Satisfaction of Students on the Use of Higher Education Services in the Case of eMPIRICA College - Puška, Adis; Berbić, Selma; Maksimović, Aleksandar (Oeconomica Jadertina, 2017)
During the last two decades, quality in higher education became increasingly important. The reasons for that can be observed in the development of the information society and globalization itself. By applying the Bologna Declaration to higher education an increase in student mobility occurred, together with the emergence of more private higher education institutions and the subsequent increase in competition. The aim of the paper is to analyze the relation between the quality of service in higher education, student satisfaction and the intent to further use these services by the students. The study was conducted at the College eMPIRICA by surveying a total of 95 students. By using factor analysis a grouping of statements in three factors was performed within the quality of services variable, while the proposed hypothesis were tested by applying a multiple regression analysis. It has been proved that the quality of higher education affects the satisfaction of students and furthers the intent of using these services, while the satisfaction of students is associated with the further intention of using these services. The results presented in this work provide an important insight into the understanding of quality in higher education and its impact on the satisfaction and intention of using these services by students.
Keywords: service quality in higher education; student satisfaction; behavioral intention; multivariate analysis